The College of The Bahamas’ Graduate Programmes and Collaborative Partnerships: 2003 to The Present - Woolward, Keithley Peter (International Journal of Bahamian Studies, 2015)
This article provides a brief overview of the College of The Bahamas’ graduate degree offerings since the establishment of the Office of Graduate Programmes in 2003. It maps the various articulation agreements, Memoranda of Understanding, and collaborations that the College has entered into with universities in North America, Great Britain and elsewhere, to facilitate a range of graduate degree programmes in diverse disciplines, such as Health Care Administration, Reading, Library and Information Science, Early Childhood and Elementary Teaching, School Counselling, and Business Administration, among others. The Office of Graduate Studies acknowledges the important connection between graduate studies and the College’s research agenda and seeks to bring coherence to programme development and the research initiatives of the institution.